PEMANFAATAN ANTIOKSIDAN ALAMI FLAVONOL UNTUK MENCEGAH PROSES KETENGIKAN MINYAK KELAPA (Jurnal Teknologi Pangan, 2013)
The rancidity that leads the quality decreasing of palm oil can be happened during the storing. This unfavorable process can be controlled by using the antioxidant. In this research the skin of red onion containing flavonol was being used as the natural antioxidant to prevent the rancidity of the palm oil. The first step is  extracting the flavonol from the skin of red onion by using water as the dissolvent for 1 – 2,5 hours. The extract was mixed into the palm oil on the  concentration  range  of  3 – 11  %.  The  next  step  is  heated  on  the  humid  temperature  to accelerate  the  rancidity.  The  mix  of  palm  oil  and  red  onion  skin  was  being  stored  for  1 – 4 days. The research result was detected by the level of oil peroxide. This number was showing the  level  of  deterioration  of  the  fat  or  oil  indicating  that  there  was  rancidity.  The  best  result was on 11 % extracting concentration of the red onion skin, 1,5 hours extracting time, 4 days storing time of the palm oil and peroxide level of 0,6144 ( SH – 92 = 1 mg O/100 g ).   _____________________________________________________________________Key word : Peroxide level, rancidity, antioxidant, skin of red onion.